Upaya Peningkatan Kompetensi Guru dalam Menyusun Silabus dan RPP Melalui Supervisi Akademik yang Berkelanjutan Di SDN 4 Sumberrejo Kab. Malang: Efforts to Improve Teacher Competence in Compiling Syllabus and RPP Through Continuous Academic Supervision at SDN 4 Sumberrejo Kab. Poor - Ismini, Karti (Pedagogia : Jurnal Pendidikan, 2017)
Each process must always include the three main activities of planning, implementation and evaluation. Similarly, what happens with teaching and learning in schools. A teacher is required to do the planning, implementation and evaluation of learning. The process of learning planning that must be done by a teacher includes the following main activities: 1) Making an annual program, 2) Making syllabus, 3) Making semester program 4) Making learning implementation plan 5) And making program of re-evaluation / evaluation. Of the five elements mentioned above, syllabus and RPP is the minimum preparation of a teacher when they want to teach. Based on the results of the analysis in the 2009/2010 academic year in SD Negeri 4 Sumberrejo, the problem of low teachers is making the planning of learning, especially the preparation of syllabus and RPP. To examine the weakness of teacher's performance in that case, research is conducted to see how far the principal supervisor's supervision step can improve teacher competence in syllabus preparation and Learning Implementation Plan.